Análise variacionista da produção da fricativa interdental surda do inglês /0/ por aprendizes brasileiros - Alves, Anilda Costa (2018)
Some studies have been conducted with the aim to analyze the acquisition process of English voiceless interdental fricative /θ/ by Brazilian speakers. Among them, we can highlight the study of Reis, 2006; Peleias, 2009; Ramos & Delatorre, 2011; Schadech & Silveira, 2013; Moreira, 2015, among others. However, few studies talk about phonological awareness development, a less recurrent approach in teaching English as L2 in regular schools in Brazil, in order to acquire the phenomenon. This way, the present study aims to analyze the production of English voiceless interdental fricative /θ/ by Brazilian speakers who received two different teaching approaches. On the one hand, students who, as in the most cases, did not obtain guidance to the phonological aspects of the target language, on the other hand, students who received instruction on the main phonetic-phonological aspects of the language, in its different levels, both in the segment and suprasgment. The study is based on Variationist Sociolinguistics, formulated by Labov (2008 [1972]); in the theoretical contribution of the Acquisition of L2 (JENKINS, 2000; ALVES, 2012) and in the acoustic theory of speech production (BARBOSA & MADUREIRA, 2015; CHIBA & KAJIYAMA, 1941; FANT, 1960)). The interface of L2 Sociolinguistics and Acquisition emerges as a new field of study that aims to analyze the multiple influencing factors in the target linguistic processing, which may be related to linguistic and extralinguistic aspects. The acoustic theory acts as an important tool in this kind of approach, since it does not leave space for possible mistakes of interpretation of the data, favoring a better precision in the analysis. The corpus of this study is consisted by 40 informants, Brazilian students of regular education of the ninth year of Elementary School II. These students constitute two distinct classes of a private school located in the state of Paraiba. To collect the data, ten words containing the English voiceless interdental /θ/ were distributed in three distinct tasks: image reading, text reading and sentence reading. The collected material was treated in PRAAT software version 5.3 (BOERSMA & WEENINK, 2014) and then analyzed quantitatively through GOLDVARB X (SANKOFF; TAGLIAMONTE; SMITH, 2005). The independent variables found were instrument type, phonological context and phonological awareness. The statistical analysis performed did not discard any of the variables analyzed by the program and the results are presented in increasing order of significance.